The Franciscan Invention of Mexican Polytheism: The Case of the Water Gods - Botta, Sergio (Studi e materiali di storia delle religioni, 2010)
This article examines the application of the polytheistic notion of deity within the Mesoamerican context and seeks to observe polytheism not only as an autonomous category, but also as a product of a colonial discourse. Polytheism emerges as a negotiation object generated by the encounter between different religious systems. In order to trace this semiotic process, the article focuses on Tláloc, a water and earth god, in order to show the strategies and practices that result in his inclusion in a polytheistic system. The article deals with the work of three Franciscans who represent the different phases of missionary strategies in New Spain: fray Toribio de Benavente Motolinía, fray Bernardino de Sahagún and fray Juan de Torquemada. (English)